(3TQM GdaQGFV GdSLGhfOjIs - (3GdLQLGfj, Ydj Hf eMeO Hf Ydj,, GdeYQha HGdTQja GdLQLGfj J (B816 (3g`s ((3eOQSI bGQj , eOQSI TjN CafOjs)
(3ChdgG (B:s
(3HYO GdHSedI ; bGd eMeO Hf YHO GdQTjO GdSLGhfOj HYO eG Jjef HGdJSejI GdMeO ddg QH GdYGdejf hMeO GdTGcQjf bGd QShd Gddg Udi Gddg Ydjg hSde (B" (3JYdehG GdaQGFV hYdehgG GdfGS aEfgG fUa GdYde(B" (3aGdaQGjV LeY aQjVIs
(3BNQgG (B:s
(3ef UGMHg eG hQK efg abO GLJeY dCe cd efgeG YTQhf hdHfJg SJhf hdehdGg YTQI hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 7s
(3eYLe GdeDdajf (B2 / 514 (3, (B515s
(3cTa GdXfhf (B2 / 12487s
(3gOjI GdYGQajf (B1 / 728s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdaQGFVs